2011
DOI: 10.1093/eurjhf/hfr074
|View full text |Cite
|
Sign up to set email alerts
|

Novel correlations between the genotype and the phenotype of hypertrophic and dilated cardiomyopathy: results from the German Competence Network Heart Failure

Abstract: A large clinical-genetic study has unravelled novel genotype-to-phenotype correlations in HCM and DCM which warrant future investigation of both the underlying mechanisms and the prognostic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 24 publications
5
75
0
3
Order By: Relevance
“…Younger age at presentation in carriers of sarcomere protein gene mutations is a common finding in many studies 37 41 4851. The presence of multiple sarcomere gene mutations (double or triple heterozygosity, compound heterozygosity or homozygosity) was associated with a younger age compared to a single mutation or to the absence of mutations in a single report 41.…”
Section: Demographic Characteristics and Family Historymentioning
confidence: 95%
“…Younger age at presentation in carriers of sarcomere protein gene mutations is a common finding in many studies 37 41 4851. The presence of multiple sarcomere gene mutations (double or triple heterozygosity, compound heterozygosity or homozygosity) was associated with a younger age compared to a single mutation or to the absence of mutations in a single report 41.…”
Section: Demographic Characteristics and Family Historymentioning
confidence: 95%
“…3 To date, positional cloning and candidate gene screening have led to the identification of numerous heterozygous mutations in more than 40 different genes, most of which encode proteins important for the structural integrity and function of cardiomyocytes, such as regulatory proteins of the sarcomere, the nuclear envelope or intracellular homeostasis. 1,2,5 In particular, defects in proteins required for force transduction and force transmission of the sarcomeric apparatus seem to promote the development of DCM.…”
Section: Introductionmentioning
confidence: 99%
“…27,28) However, recent clinical reports have shown that genes affected by mutations, such as MYH7, may determine the magnitude of structural and functional alterations in both HcM and dcM, and that other factors, such as environmental factors that stimulate the expression of HcM phenotypes, can lead to dcM phenotypes where both right and left ventricles are affected, leading to heart failure. 29,30) Thus, in some cases, dcM may occur secondarily to a progressed and end-stage HcM. 29,30) Left ventricular noncompaction cardiomyopathy that is caused by a MYH7 missense mutation such as A1766T 31) is another disease that should be recognized as characteristic in dcM patients.…”
Section: Sarcomere Proteins As a Cause Of Dcmmentioning
confidence: 99%
“…29,30) Thus, in some cases, dcM may occur secondarily to a progressed and end-stage HcM. 29,30) Left ventricular noncompaction cardiomyopathy that is caused by a MYH7 missense mutation such as A1766T 31) is another disease that should be recognized as characteristic in dcM patients. 32,33) This disease is a myocardial disorder thought to occur as a result of arrested embryogenesis and is characterized by a spongy morphological appearance of the myocardium.…”
Section: Sarcomere Proteins As a Cause Of Dcmmentioning
confidence: 99%